Crises, capital controls, and financial integration - Levy Yeyati, Eduardo, 1965- 1965- (Policy research working paper, 2008)
"This paper analyzes the effects of capital controls and crises on international financial integration, using data on stocks from emerging economies that trade in domestic and international markets. The cross-market premium (the ratio between the domestic and international market price of cross-listed stocks) provides a valuable measure of how capital controls and crises affect integration. The paper shows that, contrary to the common perception that capital controls can be easily evaded, they do affect the cross-market premium. Controls on capital inflows put downward pressure on domestic markets relative to international ones, generating a negative premium. The opposite happens with controls on capital outflows. This signals the inability of market participants to engage in perfect arbitrage, due to the segmentation of domestic markets from international ones induced by capital controls. Crises affect financial integration by generating more volatility in the cross-market premium and putting more downward pressure on domestic prices. "--World Bank web site